(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
This research investigates the multifaceted relationship underlying capital structure dynamics along with financial performance as a result of mergers and acquisitions, or M&As, in Indian banks. In the face of increasing competition, banks have deliberately embraced M&A as a strategy of improving commercial prospects and maintaining financial stability. The primary goal of this study is to examine the changes in the capital framework and financial results of banks before and after M&A transactions. The investigation, which employs a paired t-test as a method of statistical analysis, is based on a review of annual reports from selected banks over a two-year period before and after M&A transactions. The paired t-test approach allows for a thorough statistical analysis of interconnected datasets, revealing the subtle influence of M&A attempts on both bank financial performance as well as capital structure dynamics. The study’s findings have the potential to add to the current body of knowledge on organisational planning, managing finances, and capital structure optimisation. The research has practical significance for financial companies, legislators, and scholars interested in understanding the profound effects of M&A inside the arena of financial institutions that operate within fiercely competitive landscapes because it provides comprehensive insights regarding the complex consequences of banking merger and acquisition (M&A) deals on capital structure as well as financial performance. Finally, the goal of this research is to provide the banking sector with educated decision-making capabilities and strategic guidance to businesses facing heightened competition while coping with the complexities of capital structure.